Prediction of corona anxiety based on self-diagnosis in vaccinated people - Bariamnejad, Leila; Banisi, Parinaz; Barkhordari, Fatemeh; Haghani, Shima; Farhadi Afshar, Parnian; Jalilzadeh, Mahdieh; Delfanazari, Ghanbarali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
The aim of the current research is to predict corona anxiety based on self-reported illness in vaccinated people at the vaccination center. The method of the current research is quantitative and has been implemented in a descriptive-correlational way, and it is practical in terms of the purpose of this research. The study population of this research is all the people who visited the vaccination center of the Holy Prophet (PBUH) Complex of West Tehran Azad University in the fall of 1400. Among these people, 400 vaccinated people who received the second dose were selected as a sample based on the amount calculated by Gpower software in a simple random manner. Self-diagnosis and Corona anxiety tests were taken from the subject. The data were analyzed using the statistical method of multivariate analysis of covariance. The results show that corona anxiety is predicted based on self-diagnosis. There is a positive and significant effect of the path coefficient of self-care on corona anxiety (p